2019
DOI: 10.1016/j.brainres.2019.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between nesfatin-1 and oxytocin in the modulation of the swallowing reflex

Abstract: Inhibition of the swallowing reflex by nesfatin-1 2 47 Abstract 48 49 Nesfatin-1, an 82-amino acid peptide encoded by the secreted precursor nucleobinin-2 50 (NUCB2), exerts potent anorexigenic action independently of leptin signaling. This propensity has 51 propelled this peptide and its analogues as potential anti-obesity drug candidates. However, a more 52 extensive comprehension of its biological actions is needed prior to envisaging its potential use in the 53 treatment of metabolic diseases. Swallowing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…According to our results, NUCB2/nesfatin‐1 localisation in the human medullary reticular formation and pontine reticular nucleus is interesting in view of the prominent integrative role of the reticular formation in the control of the autonomic, endocrine and behavioural responses that collectively regulate energy homeostasis 3,60 . Furthermore, Sol and the neighbouring medullary reticular formation are implicated in central control of swallowing and nesfatin‐1 has been reported to modulate the swallowing reflex by acting at the brainstem 69,70 . Because there is no scientific evidence for the functional role of NUCB2/nesfatin‐1 in brainstem reticular formation, this remains to be determined.…”
Section: Discussionmentioning
confidence: 82%
“…According to our results, NUCB2/nesfatin‐1 localisation in the human medullary reticular formation and pontine reticular nucleus is interesting in view of the prominent integrative role of the reticular formation in the control of the autonomic, endocrine and behavioural responses that collectively regulate energy homeostasis 3,60 . Furthermore, Sol and the neighbouring medullary reticular formation are implicated in central control of swallowing and nesfatin‐1 has been reported to modulate the swallowing reflex by acting at the brainstem 69,70 . Because there is no scientific evidence for the functional role of NUCB2/nesfatin‐1 in brainstem reticular formation, this remains to be determined.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, mutual inhibition between the appetite-increasing peptide and satiety peptide to alter reflex swallowing is possible. Other appetite-increasing and satiety peptides also alter the swallowing reflex [5,7,8,26]. In order to elucidate the entire mechanism of swallowing regulation by appetite-regulating substances, a comprehensive understanding, including the interaction of multiple feeding-related substances, is required.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study revealed that appetite-enhancing peptides, such as ghrelin and orexin/hypocretin, suppressed reflex swallowing induced by afferent stimulation of the superior laryngeal nerve (SLN) [5,6]. Our previous study and those of others demonstrated that the injection of a satiety peptide such as glucagon like peptide-1 (GLP-1), leptin, oxytocin, or nesfatin-1 into the rat dorsal medulla suppressed reflex swallowing induced by electrical stimulation of the SLN, similarly to appetite-enhancing peptides [7][8][9]. Thus, both appetite-increasing and -satiating substances similarly suppress reflex swallowing.…”
Section: Introductionmentioning
confidence: 90%